Purified protein derivative response in type 1 diabetics - Celik, Emre; Tastan, Yucel (Annals of Medical Research, 2023)
Aim: The aims of our study were to identify the role of suppressor T1 helper cells in the immunopathogenesis of type 1 diabetes mellitus (T1D) and to investigate the purified protein derivative (PPD) response, which is a delayed type of skin sensitivity response that develops secondarily to the effect of the T1 helper cell response. Materials and Methods: Twenty-four newly diagnosed patients with T1D were included in the study (12 girls, 12 boys), and 30 (18/12) age/sex matched healthy children were included as controls. All patients underwent the PPD skin test (TST) in the first diagnostic 24–48 h (study group-1) and again 1 month after diagnosis (study group-2). The PPD response was compared with the response of healthy children. The lower limit of PPD positivity was accepted as ≥ 10 mm. Results: The mean PPD induration value taken in the study group-2 was statistically greater than both the study group-1 and the control group PPD (p=0,014, p=0.001). Regarding the increase in duration, the PPD positivity rate was statistically higher after the first month than in the control group (p= 0.005) and the initial PPD positivity rate (p=0.023). Conclusion: Interesting results emerged for the PPD response of the study group-2, because the PPD positivity rate increased over time.